Pelaksanaan evaluasi pembelajaran melalui e-learning pada pembelajaran jarak jauh di sekolah dasar - Sefa Alfira; Jenny Indrastoeti Siti Poerwanti; Sularmi sularmi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
This research aims to (1) know the planning of learning evaluation through elearning during distance learning at SD Negeri Bunderan No. 164 Surakarta; (2) know the actualization of learning evaluation through e-learning during distance learning at SD Negeri Bunderan No. 164 Surakarta. This research is qualitative phenomenological research with a method based on the philosophy of postpositivism which was carried out for grade 1 to grade 6 teachers at SD Bunderan Surakarta. The result showed that first, the teachers had carried out distance learning evaluation or school from home has some planning activities by preparing materials, learning videos and optimally utilizing the availability of online learning media such as whatsapp, google form, zoom meeting, and google meet. Second, the actualization of the evaluation of distance learning through e-learning was carried out for grade 1 to grade 6 teachers was carried out in accordance with the 2013 curriculum by taking into the time for collecting learning evaluations, assessment and appreciation, feedback into words of motivation and enthusiasm, providing remedial for students, students as well as guidance for who have not submitting assignments. Although the learning went well, there are some problems such as the indifference of students’ parents.